2012
DOI: 10.1007/s00779-012-0504-7
|View full text |Cite
|
Sign up to set email alerts
|

When privacy and utility are in harmony: towards better design of presence technologies

Abstract: Presence systems are valuable in supporting workplace communication and collaboration. These systems are effective, however, only if they are widely adopted and candidly used. User perceptions of the utility of the information being shared and their comfort in sharing such information strongly impact both adoption and use. This paper describes the results of a survey of user preferences regarding comfort with and utility of sharing presence data in the workplace; the effects of sampling frequency, fidelity, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…As alluded to previously, LSS have significant privacy issues, and in fact the primary issue was exposed in [6]. In this study, it was shown that that users are uncomfortable with a service controlling access to their location data.…”
Section: Limitations Of Prior Workmentioning
confidence: 63%
See 2 more Smart Citations
“…As alluded to previously, LSS have significant privacy issues, and in fact the primary issue was exposed in [6]. In this study, it was shown that that users are uncomfortable with a service controlling access to their location data.…”
Section: Limitations Of Prior Workmentioning
confidence: 63%
“…Over the last decade, location-and presence-sharing systems have received considerable attention from both researchers [6,8,21,22,28,29,35] and in practice [12,15,18,20]. The recent explosion in mobile computing and social networking has led to deployment of a wide range of locationsharing systems (LSSs), both stand-alone in nature (e.g., Find My Friends [14], FourSquare [15], or Glympse [18]) as well as integrated with other social networking platforms (e.g., Facebook places [12], Google Plus [20], Twitter, or Yelp).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such data can indeed yield useful generalizable insight as indicated by the utilization of hypothetical requests and scenarios by a large number of published location sharing studies (e.g., [4,14,23,24,28]), including those that employed ESM [1,6]. Moreover, the influence of simulation was evenly distributed due to the random allocation of participants to the two study conditions, leaving comparative analyses unaffected.…”
Section: Discussionmentioning
confidence: 96%
“…Although difficult to pin down precisely, these factors are typically captured in LSS that support identity-, time-, and/or location-based rules [23,26]. In addition, others have noted that privacy preferences could be predicated on the activity in which an individual is engaged [11], the individual's perception regarding the utility to the requester [4], the entropy of the current location [25], and the frequency with which location has been requested by others [24]. Efforts have been made to develop policy languages or systems capable of capturing these types of conditions to enable better end user control of location privacy [7,9,16,20,23,26].…”
Section: Privacy Policies For Location Sharingmentioning
confidence: 99%